Analysis of parasite communities and potentially pathogenic parasites in wild takin (Budorcas taxicolor) - Zeng, Xiangwen; Liu, Ruiguo; Luo, Rongyan; Li, Bingying; Liu, Jianing; Li, Zhiguo; Wang, Weichen; Cai, Lijun; Li, Mingfu; Xiao, Mei; Ma, Xiaoping (Frontiers in Veterinary Science, 2025)
BackgroundThe endangered takin (Budorcas taxicolor) faces health risks from parasitic infections, including gastrointestinal helminths and protozoa. While previous studies have explored its gut microbiome, research on parasites remains limited. Investigating parasite diversity and its effects on takin health is crucial for effective conservation.Methods59 fecal samples were collected from the Sichuan Tangjiahe National Nature Reserve, China, across elevations of 1,100–2,500 meters. The samples were categorized into four groups based on location. DNA was extracted using the CTAB method, amplified for 18S rRNA, and sent for sequencing.ResultsAnalysis of takin fecal samples from Tangjiahe revealed significant differences in eukaryotic communities among the RA, RB, RC, and RD groups. Several potentially pathogenic helminths and protozoa were identified, including Oesophagostomum, Dictyocaulus, Entamoeba, and Eimeria. Some parasites, such as Aelurostrongylus, exhibited high abundance and widespread distribution. While they are harmless to takins, they are capable of infecting other animals. The correlation between parasite abundance and plant community composition suggests that certain plants may act as vectors facilitating parasite transmission.ConclusionThis study highlights the potential impact of nematodes and protozoa on the health of the Sichuan takin population in Tangjiahe, while also examines the relationship between the dietary composition of takins and parasitic infections. This has important ecological and practical implications for wildlife conservation and health management.